Rights and Liabilities Arising from the Sale of Defective Agricultural Goods. - McEowen, Roger A. (My University, 1996)
This publication reviews the basic Uniform Commercial Code provisions governing sales of agricultural products and examines how these provisions have been treated by the courts.
MF2035_1996_04
Keywords: MF2035; Economics; Crops; MF